Evaluasi Efektivitas Intervensi pada Ibu Hamil dengan Anemia di Indonesia: Studi Literatur - Tri Riwayati Ningsih; Fitri Windari; Heni Anggraini; Dwi Rosmawati (Pelantar Press, 2024)
An in-depth understanding of the background of the problem of anemia in pregnant women in Indonesia is crucial for designing and implementing more effective intervention programs. Effective prevention and intervention programs and efforts to holistically increase nutritional awareness in society are a must to achieve positive change in overcoming anemia in pregnant women in Indonesia. To analyze more deeply the extent to which previous research has investigated interventions for pregnant women with anemia in Indonesia. This research uses the PRISMA literature review, through a digital library database that is connected to various scientific publication pages through keywords such as